DAMPAK PENERAPAN MANAJEMEN STRATEGI TERHADAP PERKEMBANGAN USAHA MIKRO DI SULAWESI SELATAN - Al Kausar; St Wardhani Bakri; Sudirman; Fajriansyah; Revoldai Agusta (LP2M IBK Nitro, 2022)
This study aims to measure how strong the influence of implementing strategic management practices and digitalization on the performance of micro-enterprises in South Sulawesi-Indonesia (Makassar, Gowa, Maros, & Pare-Pare), especially performance related to sales turnover, break-even point (BEP), and profit. This study uses quantitative methods with primary data and data sources through the interview process and questionnaires. The interview process was conducted with the heads of small and medium enterprises (micro enterprises) in South Sulawesi (Makassar, Gowa, Maros, & Pare-Pare), while the questionnaires were distributed directly to 200 respondents by survey officers. Of the 200 questionnaires distributed to respondents, 180 of them (90%) met the requirements for processing and analysis. The results showed that strategic planning had a negative and significant effect on the sales volume of micro enterprises, strategic planning had a positive and insignificant effect on the bep of micro enterprises, strategic planning had a negative and significant effect on the profits of micro enterprises, implementation strategies had a negative and no effect. significant effect on the sales volume of micro enterprises, the implementation strategy has a positive and insignificant effect on the bep of micro enterprises, the implementation strategy has a negative and insignificant effect on the profits of micro enterprises, strategic evaluation has a positive and significant effect on the sales volume of micro enterprises, strategic evaluation has positive and significant influence on the bep of micro enterprises, strategic evaluation has a negative and insignificant effect on profits of micro enterprises, the use of technology has a positive and insignificant effect on volume Micro-enterprise sales volume, the use of technology has a negative and insignificant effect on the bep of micro-enterprises, the use of technology has a positive and significant impact on the profits of micro-enterprises.